Plasticity of natural killer cells in pregnant patients infected with SARS-CoV-2 and their neonates during childbirth - Carbonnel, Marie; Daclin, Camille; Tarantino, Nadine; Groiseau, Olivia; Morin, Véronique; Rousseau, Alice; Vasse, Marc; Hertig, Alexandre; Kennel, Titouan; Ayoubi, Jean Marc; Vieillard, Vincent (Frontiers in Immunology, 2022)
The COVID-19 pandemic has occurred due to infection caused by the SARS-CoV-2 coronavirus, which impacts gestation and pregnancy. In SARS-CoV-2 infection, only very rare cases of vertical transmission have been reported, suggesting that fetal immune imprinting due to a maternal infection is probably a result of changes in maternal immunity. Natural killer (NK) cells are the leading maternal immune cells that act as a natural defense system to fight infections. They also play a pivotal role in the establishment and maintenance of pregnancy. While peripheral NK cells display specific features in patients infected with SARS-CoV-2 in the general population, information remains elusive in pregnant mothers and neonates. In the present study, we analyzed the characteristics of NK cells isolated from both neonatal umbilical cord blood and maternal peripheral blood close to the time of delivery. Phenotype and functions were compared in 18 healthy pregnant women and 34 COVID-19 patients during pregnancy within an ongoing infection (PCR+; N = 15) or after recovery (IgG+PCR−; N = 19). The frequency of NK cells from infected women and their neonates was correlated with the production of inflammatory cytokines in the serum. The expression of NKG2A and NKp30, as well as degranulation of NK cells in pregnant women with ongoing infection, were both negatively correlated to estradiol level. Furthermore, NK cells from the neonates born to infected women were significantly decreased and also correlated to estradiol level. This study highlights the relationship between NK cells, inflammation, and estradiol in patients with ongoing infection, providing new insights into the impact of maternal SARS-CoV-2 infection on the neonate